Peningkatan Aktivitas Belajar Dan Pemahaman Konsep Biologi Dengan Strategi Survey, Question, Read, Recite, Review (SQ3R) Pada Siswa Kelas XI IPA SMA Negeri 5 Kendari - Tendrita, Miswandi (Jurnal VARIDIKA, 2016)
This classroom action research is aimed at improving activities and students understanding of biological concepts by applying the strategies SQ3R. SQ3R strategies make it possible for students to learn systematically, effectively and efficiently in the face of various teaching materials. The research was done at SMA Negeri 5 Kendari, in academic year 2013/2014. The subject of the research were 42 student that registered in the second semester of the school year 2013/2014. The data collecting method were done by using interview and observation. Source data from this study was the measurement of student learning activities using observation sheet comprehension test and measurement concept that refers to indicators of understanding of the concept according to Anderson and Krathwoll in the first cycle, second cycle and third cycle. The data analysis was done by descriptive statistics. The research concludes that: 1) The percentage scoreÂ  activitiies students in first cycle is 77,08, second cycle is 82,14%, and the three cycle is 86,31%. 2) ) The percentage score understanding of the concept in first cycle is 72,62%, second cycle is 90,18%, and the three cycle is 92,62%.Â